2018
DOI: 10.3399/bjgp18x695741
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of text messages for safety netting patients with low-risk cancer symptoms: a qualitative study

Abstract: BackgroundSafety netting is an important diagnostic strategy for patients presenting to primary care with potential (low-risk) cancer symptoms. Typically, this involves asking patients to return if symptoms persist. However, this relies on patients re-appraising their symptoms and making follow-up appointments, which could contribute to delays in diagnosis. Text messaging is increasingly used in primary care to communicate with patients, and could be used to improve safety netting.AimTo explore the acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…13,[33][34][35][36] Twelve citations were studies using qualitative methods including five interview methods, [37][38][39][40][41] two questionnaire methods, 7,42 and five mixedmethod studies. [43][44][45][46][47] Of the remaining…”
Section: Resultsmentioning
confidence: 99%
“…13,[33][34][35][36] Twelve citations were studies using qualitative methods including five interview methods, [37][38][39][40][41] two questionnaire methods, 7,42 and five mixedmethod studies. [43][44][45][46][47] Of the remaining…”
Section: Resultsmentioning
confidence: 99%
“…Another advantage mentioned was the speed of communication provided by the technology. This advantage was cited by only one of the respondents (12.5%) of this research, but was cited by most of the interviewees from other studies [22][23][24] .…”
Section: Discussionmentioning
confidence: 80%
“…Among the disadvantages related to WhatsApp in the doctor-patient relationship mentioned by the interviewees is the trivialisation of the medical service by the patients (25%). Another study 22 demonstrated that, in fact, more accurate clinical data are necessary for good care and many times the data can not be sent using the application (due to lack of resource or knowledge of the person passing the information). This justifies the dissatisfaction of doctors with a service centred solely on the exchange of messages online.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One virtue of seeding an idea like safety netting into the mind in an unfinished form is that, like a grain of sand in an oyster, it can niggle something unexpected and valuable into existence. The paper by Hirst and Lim, 7 where they describe using text messaging to follow up patients who presented with possible cancer symptoms, is an example. By hitching a common clinical anxiety to a popular technology, they have created an innovation that 'early adopter' GPs will enjoy developing, and that will probably save some lives.…”
Section: The Three 'Thinking Ahead' Questionsmentioning
confidence: 99%